Terapi Applied Behavior Analysis Meningkatkan Kemampuan Interaksi Sosial pada Anak Autisme Umur 7-12 Tahun - Mochamad Heri; Komang Gde Trisna Purwantara; Putu Agus Ariana (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of applied behavior analysis therapy on social interaction in children with autism aged 7-12 years at SDLB SLB Negeri 2 Buleleng. The type of this research is pre-experimental research with one group pre-post test design. The results of the univariate analysis, most of the respondents were male 53 respondents (85.5%), the level of moderate social interaction was 46 respondents (74.2%) autistic children before being given treatment, and the high level of social interaction was 40 respondents (64, 5%) autistic children after being given treatment. The results of this study indicate an effect of Applied Behavior Analysis therapy with a high level of social interaction totaling 40 respondents (64.5%) of autistic children after being given treatment. The results of data analysis with the Wilcoxon test get a value of 0.000 or p <Î± (0.05). In conclusion, Applied Behavior Analysis therapy has an effect on social interaction in children with autism aged 7-12 years at SDLB SLB Negeri 2 Buleleng. Keywords: Applied Behavior Analysis, Autism, Social Interaction